(3GdYdd aj SQ GdWHjYIs - (3HdjfGS GdMcjes
(3ChdgG (B:s
(3hceG bdJ Ydi Ydd OhQJGf Gdadc hcjfhfJg hJbdH Gddjd hGdfgGQ s
(3BNQgG (B:s
(3Cf eG ai GdYdh eJUd HeG ai GdSad dGf GdCTjGA Jchf Ydi CLfGSgG hJJUd HCTcGdgG s
(3GdebGdI GdKGdKI Yf GdeYGOfs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B- (3eOQjO s
Keywords: (3GdadSaI hGdefWbs